2019
DOI: 10.1007/s00167-019-05753-3
|View full text |Cite
|
Sign up to set email alerts
|

The femoral posterior fan-like extension of the ACL insertion increases the failure load

Abstract: Purpose To examine the role of the posterior fan‐like extension of the ACL's femoral footprint on the ACL failure load. Methods Sixteen (n = 16) fresh frozen, mature porcine knees were used in this study and randomized into two groups (n = 8): intact femoral ACL insertion (ACL intact group) and cut posterior fan‐like extension of the ACL (ACL cut group). In the ACL cut group, flexing the knees to 90°, created a folded border between the posterior fan‐like extension and the midsubstance insertion of the femoral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…This study showed no significant differences in failure loads between the anterior portion (direct insertion) and the posterior portion of the ACL femoral insertion site (mainly consisting of indirect insertion) in 30 degrees of flexion. This result agrees with that of a previous biomechanical study on the femoral posterior fan-like extension of the ACL [13]. This implies that the indirect insertion of the ACL [7], the so-called fan-like extension fibers [8], significantly contributes to ACL strength.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study showed no significant differences in failure loads between the anterior portion (direct insertion) and the posterior portion of the ACL femoral insertion site (mainly consisting of indirect insertion) in 30 degrees of flexion. This result agrees with that of a previous biomechanical study on the femoral posterior fan-like extension of the ACL [13]. This implies that the indirect insertion of the ACL [7], the so-called fan-like extension fibers [8], significantly contributes to ACL strength.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, our histological study showed that the porcine ACL femoral insertion site consisted of direct and indirect insertions in the anterior and posterior portions, respectively; this histological structure is also similar to that of humans [6,7]. Therefore, the porcine knee is considered to be the preferred model for experimental biomechanical studies [25], since it can be matched by size and age [13]. Human cadaver knees are difficult to obtain at younger ages, at which ACL injuries occur.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Incidental histologic studies proved that the femoral ACL insertion area had spread more distally and posteriorly into the region called the area of indirect insertion or fun-like extension fibers. 30 , 31 , 32 The fan-like extension fibers significantly functioned with increasing ACL failure load. 30 According to the modified definitive area of ACL fiber attachment, the accuracy of our modified double-bundle transtibial tunnel creation technique was estimated at 92.6% of the anatomic tunnel creation.…”
Section: Discussionmentioning
confidence: 97%
“… 30 , 31 , 32 The fan-like extension fibers significantly functioned with increasing ACL failure load. 30 According to the modified definitive area of ACL fiber attachment, the accuracy of our modified double-bundle transtibial tunnel creation technique was estimated at 92.6% of the anatomic tunnel creation.…”
Section: Discussionmentioning
confidence: 97%